Du calcul biophysique à l’évaluation des risques financiers - Sylvain Maechler; Valérie Boisvert (Revue de la Régulation)
The interactions between the economy and nature are little reflected in the management tools of capitalism. The impacts on the latter remain largely invisible to economic processes. This is the narrative behind the proposal to integrate nature into a central instrument of capitalism: accounting. However, nature accounting is shaped by a diversity of actors, practices, objectives and effects. Taking a chronological approach, we show how three successive approaches that we call “accounting worlds” have developed over time and coexist today. The first is public accounting expressed in biophysical, material and energy units, with the aim of exposing the exploitation and unequal exchange of natural resources as an extension of unbalanced trading relations. This was followed by the gradual development of natural capital monetary accounting projects, aimed at internalizing environmental externalities, initially at the national level and later extended to private accounting. A third and final project has recently emerged in connection with traditional accounting and financial standards. Its purpose is to assess the impact of nature and its degradation on the economic and hence financial performance of firms. Based on an analysis of these three worlds, we suggest that the growing influence of accounting thought and practices on nature, especially in their most recent forms, leads not so much to its commodification or financialization as to its invisibility or dilution in the logic of financial capitalist reproduction. Finally, we question the possible emergence of a unified regime of accounting for nature.